Pemanfaatanan Tepung Umbi Lokal Sebagai Filler Bakso Ditinjau dari Kualitas Fisiko-kimia dan Organoleptik: The Utilization of Local Tuber Flour as a Meatball Filler Reviewed from Physico-chemical and Organoleptic Quality - Mudawaroch, Roisu Eny; Rinawidiastuti, Rinawidiastuti (Fakultas Peternakan Universitas Jambi, 2025)
Background: Meat is the main ingredient in making meatballs. In addition to meat, important ingredients are fillers and binders (emulsifiers). Fillers and emulsifiers that are filled in meatballs are usually tapioca flour. Local Indonesian tubers that have not been widely utilized are gembili, ganyong, taro and suweg. Flour from local tubers can be used as a substitute for tapioca flour in making meatballs. Objective. Purpose: The purpose of this study was to determine the effect of local tuber level substitution on the physicochemical and organoleptic quality of meatballs. Methods: The main ingredients in this study were meatballs, gembili, taro, ganyong, porang, tapioca flour. This study used 13 treatments, namely substitution of local tuber flour levels (gembili, taro, ganyong, porang) with tapioca flour. All treatments were repeated 3 times. Research parameters Data were obtained from the physicochemical quality test, namely pH, water content, cooking loss, water holding capacity, and sensory quality, namely the hedonic scale and hedonic test. The data obtained were analyzed by analysis of variance (ANOVA). If there is a difference, it is continued with Duncan's multiple range test. Results: Physico-chemical quality, namely pH, water content, cooking loss, water holding capacity showed a very significant effect (P <0.01). The water content of meatballs ranged from 66.56-70.61%, cooking loss ranged from 2.93-5.90, and pH ranged from 6.06-6.26. Organoleptic quality on the hedonic scale showed a very significant difference (P <0.01) in color and elasticity. The hedonic test showed a very significant effect (P <0.01) in elasticity. Conclusion: Substitution of local tuber levels on a very significant effect on physico-chemical quality, and significantly different on the hedonic scale of color and elasticity, and a very significant effect on the hedonic test of elasticity.